Navigating mental health conversations - Shannon Habba; David Frond; Kyle Burghardt; Brittany Stewart (INNOVATIONS in Pharmacy, 2025)
Background: Community pharmacies offer a unique and accessible opportunity to close the existing mental health care gap. Many pharmacists and student pharmacists, however, lack the confidence to effectively engage in conversations regarding mental health. The objective of this study was to assess student pharmacist confidence and knowledge in navigating mental health conversations after Mental Health First Aid (MHFA) training alone versus MHFA training paired with experiential learning opportunities through community pharmacy-based depression screening events.